2017
DOI: 10.3847/1538-4365/aa813e
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Core Conditions of the Earth and Super-Earths Using Intense Ion Beams at FAIR

Abstract: Using detailed numerical simulations, we present the design of an experiment that will generate samples of iron under extreme conditions of density and pressure believed to exist in the interior of the Earth and interior of extrasolar Earth-like planets. In the proposed experiment design, an intense uranium beam is used to implode a multilayered cylindrical target that consists of a thin Fe cylinder enclosed in a thick massive W shell. Such intense uranium beams will be available at the heavy-ion synchrotron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The number of photons per pulse N is (12) and is equivalent to ∼10 12 for the peak energy per pulse (3.5 mJ) and x-ray energy (25 keV) simulated here, which are close to the facility maxima (Table I). In our models we specify E pulse (Eq.…”
Section: Please Cite This Article Assupporting
confidence: 54%
See 2 more Smart Citations
“…The number of photons per pulse N is (12) and is equivalent to ∼10 12 for the peak energy per pulse (3.5 mJ) and x-ray energy (25 keV) simulated here, which are close to the facility maxima (Table I). In our models we specify E pulse (Eq.…”
Section: Please Cite This Article Assupporting
confidence: 54%
“…Such practical challenges of using radiation heating to study equilibrium warm dense matter in the laboratory often complicate the experimental study of equilibrium extreme systems common in nature and technology. Other methods of irradiative volumetric energy deposition providing access to similar states of matter have similar limitations, include intense proton 4,11 , heavy ion 12 , and electron 8 beams. Dynamic compression, the driving of compression (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown in Ref. [] that intense laser‐driven hard X‐ray radiography along the cylinder axis can be used to measure the line density along the length of the sample. Simulations have shown that the implosion is quasi‐one‐dimensional.…”
Section: Discussion Of Diagnosticsmentioning
confidence: 99%
“…This makes it practically challenging to use isochoric heating to study equilibrium warm dense matter, as needed to accurately simulate the true conditions of many high energy density systems in nature and technology. Other often-used methods of irradiative volume or bulk energy deposition providing access to similar states of matter include intense proton 2,8 , heavy ion 9 , and electron 5 beams or other modes of fast electron deposition 3,10,11 . Dynamic compression, the driving of compression waves travelling at near sound velocities (∼1-10 µm/ns), is a somewhat slower form of volumetric energy delivery, while diffusive (as opposed to ballistic) heat conduction is even slower.…”
Section: Introductionmentioning
confidence: 99%